The Last Sasanians in Eastern Iran and China - Pashazanous, Hamidreza; Afkande, Ehsan (Anabasis. Studia Classica et Orientalia, 2014)
Following the devastating defeat at Nihawand, the last Sasanian emperor, Yazdegerd III (632–651) sought refuge in the eastern Iranian plateau, although he continued to return to his country to exert influence over the Persian nobility until his death. His sons, Pērōz and Wahrām, along with a few Persian nobles took refuge in the Tang court of imperial China. They constantly tried to regain “Ēranšahr” (Persia) from the Arabs with the assistance of the Chinese, Sogdians, and the inhabitants of Tocharistan, but all their attempts were in vain. Information about Yazdegerd and his sons and the time they spent in Central Asia and at the Tang court is recorded in the works of Muslim authors, in later Middle Persian literature, and in Chinese sources. In what follows, we will offer some fresh insights about these accounts as they relate to the final years of the Sasanian empire and afterwards.